EVASÃO ESCOLAR: AÇÕES GOVERNAMENTAIS E A NEGAÇÃO DO ACESSO E PERMANÊNCIA NO ENSINO MÉDIO NO BRASIL NO PERÍODO DE 2016 A 2019 - Granetto, Karen Brustolin (2022)
The object of study of this dissertation is the school dropout in Brazilian High School, comprising the period from 2016 to 2019, especially in relation to access and permanence, to consider socioeconomic conditions. The research reflects on the evidence and trends, socially addressed, that produce the school dropout in Brazilian High School, through the following research problem: what are the evidence and trends regarding the process of permanence or school dropout in Brazilian High School, in the period from 2016 to 2019? From the research problematic, the general objective was defined as follows: to understand the evidence and trends in relation to the permanence or school dropout in Brazilian High School, in the period from 2016 to 2019. To this end, a bibliographic and documentary research was conducted, with a qualitative basis, which comprised analyses that contemplated the legal devices prescribed in the Federal Constitution of 1988 and the Law of Directives and Bases of Education – LDB – Law nº 9.394/1996, as well as other documents pertinent to the theme, in addition to educational data collected from official websites of the Federal Government and research institutions. We conclude that the evidences found refer to high dropout rates in Brazilian High School, in the period from 2016 to 2019, and the trends point: to the increase of students evaded from school, in a way that denotes the socioeconomic inequality aggravated by the covid-19 pandemic; to the absence of certain contents to the development of critical thinking; to the conformation of young people to a society in which formal jobs become increasingly scarce or transmuted into underemployment; to the continuity of economic, social and educational policies guided by the neoliberal ideology, which arrived in Brazil at the end of the 1980s and settled more strongly from the 1990s. Finally, school dropout is the result, among other issues, of socioeconomic inequalities, of the concrete conditions in which the subject is inserted. In this sense, to establish the relationship between permanence and dropout in Brazilian high schools, it is essential to consider the material conditions of production of life and their determinants in the contemporary social context